The Anchorage of Technology at Maritime English Class: A Case Study at Barombong Maritime Polytechnic - Nursyam; Ratno; Rony (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2025)
This research examines the significant role of technology in education at Barombong Maritime Polytechnic, particularly in teaching Maritime English. Using a mixed-methods approach that combines qualitative and quantitative analysis, the research examines how technology affects the effectiveness and engagement in Maritime English learning. The findings underscore the crucial role of technology at various stages of learning, from preparation to evaluation. The use of technology, including compiling e-books, leveraging YouTube for content delivery, and utilizing the Marlin Test app, demonstrates a wide range of applications in enhancing learning outcomes. Throughout the learning process, the frequent utilization of technology-based tools and platforms fosters an interactive and supportive learning environment conducive to effective learning. From computers and projectors to applications such as Wordwall and Zoom Meeting, technology enriches the educational experience, provides access to a variety of resources, and facilitates collaboration between students and educators. Additionally, technology-supported evaluation methods, such as Google Forms for theory exams and video recording for speaking assessments, offer a more efficient and comprehensive approach to assessing student progress and proficiency.